Determinants of credit card misuse among Gen Y consumers in urban Malaysia - Zainudin, Rozaimah; Mahdzan, Nurul Shahnaz; Yeap, Ming Yee (Emerald, 2019)
Purpose: The concept of “buy now pay later” leads Malaysian Generation Y (Gen Y) to excessively use their credit cards for spending. To gauge the extent of this worrisome scenario, the purpose of this paper is to attempt to investigate the factors, including credit attitudes, knowledge on credit card, materialism, social norm and self-efficacy, that influence credit card misuse amongst Gen Y in Malaysia. Design/methodology/approach: The authors have collected responses from a total of 501 respondents in two urban areas in Malaysia and estimated six multiple regression models to test five hypotheses. Findings: The results suggest that credit card knowledge and self-efficacy are negatively related to credit card misuse amongst Gen Y in Malaysia. In contrast, positive relationships were found to exist between credit card attitudes, materialism and social norm and the dependent variable. Research limitations/implications: In this study, the authors limit the data collection to the two biggest urban areas in Malaysia, namely, Klang Valley and Ipoh. Practical implications: For the regulator’s perspective, the results can be used to understand the alarming indebtedness behaviour amongst working members of Gen Y and outline appropriate and effective policies to reduce their serious indebtedness. Financial service providers, however, can collaborate with regulators to curb credit card misuse amongst Gen Y, so that the latter can avoid high bad debt from line of credit facilities and bankruptcy. Originality/value: The study’s findings will further enrich the existing literature on the factors affecting the credit card misuse, especially for the unique Gen Y cohort in Malaysia.